The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1992
DOI: 10.1016/0304-3959(92)90040-i
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in neuronal excitability and the potency of spinal mu, delta and kappa opioids after carrageenan-induced inflammation

Abstract: These electrophysiological results show that the development of inflammation following peripheral injection of carrageenan into the paw is accompanied by alterations in the magnitude of the C-fibre evoked response of multireceptive dorsal horn neurones. The evoked response of the dorsal horn cells was found to either increase or decrease in the 3 h following the carrageenan injection, and the direction of this change was related to the degree of wind-up exhibited by the cell. Regardless of whether a cell was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
3
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 38 publications
6
73
3
3
Order By: Relevance
“…In the same study, morphine was found to be considerably more potent in the inflamed animal when compared to normal rats, suggesting that there appears to be a reduced availability of CCK in the spinal cord following carrageenan-inflammation (Stanfa et al, 1992;Stanfa & Dickenson, 1993). Both the failure of CCK antagonists to potentiate the action of morphine and the increased potency of morphine in the carrageenan inflammation model are in disagreement with the observations of the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…In the same study, morphine was found to be considerably more potent in the inflamed animal when compared to normal rats, suggesting that there appears to be a reduced availability of CCK in the spinal cord following carrageenan-inflammation (Stanfa et al, 1992;Stanfa & Dickenson, 1993). Both the failure of CCK antagonists to potentiate the action of morphine and the increased potency of morphine in the carrageenan inflammation model are in disagreement with the observations of the present study.…”
Section: Discussioncontrasting
confidence: 77%
“…Upregulation of its receptors results in decreased analgesia in some neuropathic models; decreased CCK concentrations, in inflammatory models, results in enhancement of mu receptor effects. 88 Alternatively, antagonists of the CCK receptor may enhance the analgesic action of opioids. 89,90 It has been shown that NMDA receptor activation results in formation of nitric oxide (NO).…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 99%
“…Similarly, the reduced effectiveness of opioids in neuropathic pain has been attributed to a decrease in spinal opioid receptors (Kohno et al, 2005) and to increased spinal CCK release. (Wiesenfeld-Hallin et al, 2002) Enhanced opioid analagesia during inflammation has been well established for peripherally (Stein et al, 2001), systemically (Kayser & Guilbaud, 1983;Joris et al, 1990) and spinally (Hylden et al, 1991;Stanfa et al, 1992) administered opioids. While i.t.…”
Section: Introductionmentioning
confidence: 99%